‘A Ghastly and Blasphemous Nightmare’: Environmental Ethics in Dickens’s Journalism - Ignacio Ramos-Gay (Baltic Journal of English Language, Literature and Culture)
In the article ironically entitled A Monument of French Folly, published in Household Words, 8th of March, 1851, Charles Dickens targeted a number of civic reforms in municipal abattoirs located within the city walls of London as well as the English arrogant reluctance to adopt the hygienic measures practiced in French slaughterhouses. Dickens’s article was part of the foregoing struggle to relocate the Smithfield livestock market and surrounding slaughterhouses from the City of London in the city outskirts, so as to prevent ventilation problems and the risk of miasmic infection. The aim of this paper is to examine Dickens’s article in the light of contemporary environmental concerns. I will particularly focus on his journalism as a token of modern social-ecology and environmental ethics, as shown by the administration and government policies he suggests to be implemented.